PENGEMBANGAN SISTEM PEMROSESAN TRANSAKSI ADMINISTRASI AKADEMIK PERGURUAN TINGGI MELALUI INTERNET - Samsul Hadi (Universitas Negeri Yogyakarta, 2000)
The purpose of this research was to developed a web-based transaction processing system of higher education academic administration that considered dota security. The system consisted of*ee parts ofsofiware, one for network administrator, one other for student. The function for academic administrator staff, and the of each part should consider the user authorization. This research used Windows 97 operating system. Microsofi Access 97, l|/ebBase 4. 10 build 57, and a computer supported the software that was ready to be connected to computer network. Thirteen tables were built to store data. The system soJtware was written in ITML, WebBase macro, and SQL to modify data in the tables. The sofiware was saved in htf files that could be accessed with browser. The research expecte d system could /unction we ll.",